Strategi Pengelolaan Dana Infak (Program Koin NU) Di Lembaga Amil Zakat, Infak Dan Sedekah Nahdlatul Ulama Kota Samarinda - Hasbi, Muhammad; Darmawati, Darmawati; Mahrus, Moh (Al-Tijary, 2022)
The background of the problem in this study is departing from the lack of public knowledge about the potential of infak funds. This research is to find out the LAZISNU Kota samarinda strategy in managing infak funds through the KOIN NU program and also the role of the institution in increasing the productive business of beneficiaries of infak funds. This research method is a type of field research with a descriptive qualitative approach. Data and data sources have 6 key informants and 2 main key informants. The research results obtained from this study are the management strategies carried out showing the effort to succeed the KOIN NU program, namely by collecting funds from NU congregations in Samarinda City coordinated by one person collectors in each of their assemblies and cooperation with food and food stalls to entrust KOIN NU cans, in management it cannot be said professionally because in reality only one of the management from LAZISNU Kota Samarinda and MWCNU in Palaran Sub-District who also collect, count and make monthly financial reports, while for the distribution of the four pillars of the central management program, namely the fields of education, health, economics and disaster preparedness and allans have been carried out according to ability. Implications of the research for increasing productive businesses that have been implemented by LAZISNU Samarinda with strategies to build public trust through management of LAZISNU Samarinda which is able to compete with private LAZ and plays an important role in collecting infaq funds.